Effect of Feed Form and Whole Grain Feeding on Gastrointestinal Weight and the Prevalence of Campylobacter jejuni in Broilers Orally Infected. - Marta Isabel Gracia; Jaime Sánchez; Carlos Millán; Óscar Casabuena; Peter Vesseur; Ángel Martín; Francisco Javier García-Peña; Pedro Medel (PLoS ONE, 2016)
Two independent trials were carried out to evaluate the effect of feed form, whole wheat (WW) and oat hulls (OH) addition on gastrointestinal (GIT) weight and Campylobacter jejuni colonization in orally infected birds. In Trial 1, there were six treatments factorially arranged with two feed forms (mash vs pellets), and three levels of WW from 1-21/22-42d: 0/0, 7.5/15%, 15/30%. Broilers were allocated in cages (3 birds/cage, 12 cages/treatment). In Trial 2, there were three treatments: a mash diet, a mash diet including WW (7.5% from 1-21 and 15% from 22-42d), and a third treatment including also 5%OH. Broilers were allocated in floor pens (1 pen with 30 birds/treatment). At 14d, all broilers in Trial 1 or 3 broilers/pen in Trial 2 were orally challenged with 1.5 x 105 cfu of C. jejuni ST-45 /. In Trial 1, birds fed pelleted diets consumed 13.5% more feed, gained 31% more weight, and presented 12.9% better feed conversion for the whole trial (P<0.05). Pelleting decreased the relative weight of GIT and gizzard and increased the relative weight of proventriculus (P<0.05). Mash diets decreased pH in the gizzard (P<0.05). Inclusion of WW decreased the relative weight of proventriculus, increased gizzard weight, and reduced pH in the gizzard (P<0.05). At 21d of age, mash tended to reduce C. jejuni compared to pellets (7.85 vs 8.27 log10cfu/g; P = 0.091) and WW inclusion at 7.5/15% reduced C. jejuni colonization when compared to lower and higher inclusion (P<0.05). In Trial 2, birds fed T3 (WW+OH) showed 1.38 log10cfu/g less than birds fed Control diet (P<0.05). In conclusion, despite of the clear morphological changes in the GIT derived of FF and WW inclusion, no clear reductions in C. jejuni populations in the ceca were observed. However, WW and OH inclusion to mash diets significantly reduced cecal C. jejuni colonization at 42 days.